2002
DOI: 10.1038/sj.bjp.0704962
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal‐dependent recruitment of Na+,K+‐ATPase to the plasmalemma is mediated by PKCβ and modulated by [Na+]i

Abstract: The present study demonstrates that stimulation of hormonal receptors of proximal tubule cells with the serotonin‐agonist 8‐hydroxy‐2‐(di‐n‐propylamino) tetraline (8‐OH‐DPAT) induces an augmentation of Na+,K+‐ATPase activity that results from the recruitment of enzyme molecules to the plasmalemma. Cells expressing the rodent wild‐type Na+,K+‐ATPase α‐subunit had the same basal Na+,K+‐ATPase activity as cells expressing the α‐subunit S11A or S18A mutants, but stimulation of Na+,K+‐ATPase activity was completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…1A). We have previously demonstrated that 8-OH-DPAT, a serotonin 1A receptor agonist, and the phorbol ester PMA, an activator of protein kinase C, stimulate the same signaling pathway as Ang II to induce the plasma membrane recruitment of NKA molecules (32). Consistent with this observation, the substitution of Tyr-255 for phenylalanine in NKA ␣1 impairs the stimulation of NKA activity by either 8-OH-DPAT or PMA (Fig.…”
Section: Resultssupporting
confidence: 65%
“…1A). We have previously demonstrated that 8-OH-DPAT, a serotonin 1A receptor agonist, and the phorbol ester PMA, an activator of protein kinase C, stimulate the same signaling pathway as Ang II to induce the plasma membrane recruitment of NKA molecules (32). Consistent with this observation, the substitution of Tyr-255 for phenylalanine in NKA ␣1 impairs the stimulation of NKA activity by either 8-OH-DPAT or PMA (Fig.…”
Section: Resultssupporting
confidence: 65%
“…A representative Western blot of five experiments is shown. B, co-immunoprecipitation of the Na ϩ ,K ϩ -ATPase with 14-3-3 protein was performed exactly as described above for A in OK cells stably transfected with the Na ϩ ,K ϩ -ATPase bearing the mutation Ser 11 3 Ala (S11A), Ser 18 3 Ala (S18A), or deletion of the first 26 amino acids (⌬26) in the ␣ 1 -subunit, as described by Chibalin et al (8) …”
Section: Resultsmentioning
confidence: 99%
“…In the rodent renal epithelia, phosphorylation of Na ϩ ,K ϩ -ATPase ␣ 1 -subunits (at that are present at the plasma membrane is necessary for dopamine (DA) 1 -induced endocytosis (6 -8) and (at Ser-11) for parathyroid hormoneinduced endocytosis (9). In contrast, recruitment of new molecules to the plasma membrane in response to angiotensin II (10) or serotonin (11) requires the phosphorylation of Na ϩ ,K ϩ -ATPase molecules (Ser-11/Ser-18) present within endosomes. DA-mediated phosphorylation of the ␣ 1 -subunit and Na ϩ ,K ϩ -ATPase endocytosis requires activation of the PKC-isoform, whereas serotonin-and angiotensin II-dependent increase in Na ϩ ,K ϩ -ATPase activity requires activation of the PKC-␤ isoform (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the turnover rate) of the pumps already present at the plasma membrane, as well as by modulating Na + /K + pump expression at the cell surface (Therien and Blostein, 2000). The latter is accomplished by recruiting an intracellular protein pool of the pump to the plasma membrane, and by internalization of the plasma membrane-associated pool (Barlet-Bas et al, 1990;Chibalin et al, 1999;Gonin et al, 2001;Budu et al, 2002;Efendiev et al, 2003;Vinciguerra et al, 2003;Efendiev et al, 2007). Our previous findings (Nikolić et al, 2012) and results obtained in the present study indicate that the SMF-induced increase in Na + /K + pump activity can be mediated through short-term mechanisms of pump activity regulation.…”
Section: Discussionmentioning
confidence: 99%